Excessive weight loss after sleeve gastrectomy: a systematic review - Fischer, Lars; Hildebrandt, Caroline; Bruckner, Thomas; Kenngott, Hannes Götz; Linke, Georg R.; Gehrig, Tobias; Büchler, Markus W.; Müller, Beat P. (Obesity surgery, 2012)
BackgroundThe clinical significance of sleeve gastrectomy (SG) as a primary bariatric intervention is still under debate. This article aims to systematically analyze excessive weight loss (EWL) in patients after SG.MethodsA systematic literature search on SG from the period January 2003 to December 2010 was performed. Data described from systematic reviews dealing with gastric bypass procedures was used as comparator.ResultsThe final study included 123 papers describing 12,129 patients. Most of the papers describe EWL at 12 months (43.9% of all papers). For SG, the maximum EWL occurred 24 and 36 months postoperatively with a mean EWL of 64.3% (minimum 46.1%, maximum 75.0%) and 66.0% (minimum 60.0%, maximum 77.5%), respectively. At 12 months, the mean EWL in patients receiving SG was significantly lower when compared to patients who underwent gastric bypass (SG 56.1%, gastric bypass 68.3%; p < 0.01, two-sided Wilcoxon test). Although patients with gastric bypass still had higher EWL rates at 24 months compared to patients after SG, these differences were not significant (SG 61.3%, gastric bypass 69.6%; p = 0.09, two-sided Wilcoxon rank-sum test). Reoperations after SG are necessary in 6.8% (range 0.7-25%) of cases with patients receiving SG as a stand alone procedure and in 9.6-28.5% of cases with patients undergoing SG as a planned first stage procedure.ConclusionsSG is an effective bariatric procedure with a lasting effect on EWL. Compared with gastric bypasses, there is no difference in EWL at the time point of 24 months.